The Role of International Arbitration in Maintaining World Peace and Security with an Emphasis on Non- State Actors - Erfan Mirzazadeh; Seyyed Ghasem Zamani; Mohsen Mohebi; Fathollah Rahimi (پژوهشهای حقوقی)
The role of international arbitration in maintaining world peace and security has been largely through the peaceful settlement of international disputes as well as the development of arbitration precedents regarding international law governing the settlement of international disputes. Today, the growing role of non-state actors as new subjects of international law has become increasingly important. In addition, international and non-governmental organizations have played a constructive role in the gradual development of international law. In this study, by examining some important international arbitration cases, we seek to answer the question of How the International Arbitration has been influential in resolving disputes between governments and non-governmental actors and non-governmental actors with each other, in maintaining world peace and security and in developing international law. After analyzing the practice of international arbitration, the author comes to the general conclusion that when diplomatic efforts to resolve disputes are fruitless, the best and most effective solution is to refer to arbitration. In fact, the arbitration can resolve the dispute at an early stage and prevent it from escalating into hostilities. Accordingly, at the end of this research, suggestions addressed to the diplomatic system are also presented.